A combined of fuzzy TOPSIS with z-number and alpha-cut for decision making problems - Nurnadiah, Zamri; Yahia Ibrahim, Awajan Khaleel (2019)
The most famous method when dealing with decision making is Multi-Criteria Decision Making (MCDM). One of the easiest techniques from MCDM is Fuzzy Technique for Order Preference by Similarity to Ideal Solution (FTOPSIS). However, there are some circumstances in FTOPSIS still needs to be enhanced. Therefore, this paper concentrates on: (1) to develop FTOPSIS with Z-number and α-cut based MCDM problem; the combination of Z-Number and α-cut is seen suitable to solve uncertainty issue due to the additional restriction and reliability parts; (2) to validate the propose method using numerical example. The study presents six steps of FTOPSIS with Z-numbers and α-cut to verify the position of the numerical example; (3) to evaluate the efficiency of the proposed method using ten different number of α-cut. Ten different numbers are 0.1 to 0.9. From the study, this proposed method opens a new revolution in MCDM area to provide different ways when dealing with decision making problems. Thus, give us variety of techniques in decision making area.